Enhancing Third Grade Students’ Learning Outcomes in Science and Social Studies Through Game-Based Learning: A Classroom Action Research - Sari, Meirita; Yunilarosi, Elvida Sari; Ula, Siti Mubarokatul; Panse, Vishal R.; Shukla, Alok; Omanwar, Shreeniwas (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
The low learning outcomes of third-grade students at SDN 2 Rambang in Science learning. Therefore, innovation through game-based learning is needed. This research aims to improve the learning outcomes of third-grade students at SDN 2 Rambang on the topic of the life cycle of living things in Science learning using the game-based learning method. The subjects of this research were 19 third-grade students at SDN 2 Rambang. The method used in this research was Classroom Action Research which was carried out in 2 cycles. The instruments used included observation sheets, learning outcome tests, and documentation. The results of the research showed that the application of the game-based learning method could improve student learning outcomes. In the pre-cycle, only 6 out of 19 students (31.6%) achieved scores above the Minimum Completeness Criteria. In the first cycle, this increased to 12 students (63.2%), and in the second cycle, it further increased to 19 students 100%). In addition to the increase in learning outcome scores, students also showed increased motivation, activeness, and understanding of the material. Thus, it can be concluded that the game-based learning method is effective in improving student learning outcomes in Science learning, especially on the topic of the life cycle of living things.